Effect of rooftop photovoltaics (PV) on power systems - Ng, Joshua Yu Han (Nanyang Technological University, 2021)
In this project, the effects of rooftop PV on the power systems has been examined and discussed. With technology improving, the demand for energy has increased. This has caused many to be perturbed by what are the effects of the rising demand of energy on global warming, prompting an increase in the search for answers in the form of renewable energy resources. Solar energy is considered one of the main sources of renewable energy and rooftop PV is one of the main forms of solar energy conversion that is used in Singapore due to her size and density. Therefore, it is important that people are able to understand the technologies used in harvesting solar energy to meet our energy demands. This final year project report covers what are the effects of rooftop PV and discusses the effects of rooftop PV on the power grid.